2021
DOI: 10.1136/bmjno-2021-000211
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and tension-type headache among undergraduate medical, dental and pharmaceutical students of University of Aleppo: a cross-sectional study

Abstract: IntroductionHeadache disorders are among the most common 10 causes of disability worldwide according to the global burden of disease survey 2010. Headache is also wildly common among universities students when compared with other populations. The purpose of this study is to assess headache prevalence among Aleppo University medical, dental and pharmaceutical undergraduate students.MethodsA questionnaire-based cross-sectional study was conducted among medical, dental and pharmaceutical students at Aleppo Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
4
10
0
Order By: Relevance
“…Only 23.7% of study participants reportedly sought medical advice. These results were in line with other previous studies published around the world [ 14 , 33 , 34 , 35 ]. For instance, Alkarrash et al found that, among undergraduate students at the University of Aleppo, 15.9% sought medical attention [ 35 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Only 23.7% of study participants reportedly sought medical advice. These results were in line with other previous studies published around the world [ 14 , 33 , 34 , 35 ]. For instance, Alkarrash et al found that, among undergraduate students at the University of Aleppo, 15.9% sought medical attention [ 35 ].…”
Section: Discussionsupporting
confidence: 94%
“…These results were in line with other previous studies published around the world [ 14 , 33 , 34 , 35 ]. For instance, Alkarrash et al found that, among undergraduate students at the University of Aleppo, 15.9% sought medical attention [ 35 ]. Similarly, Panigrahi et al reported that 10% of undergraduate students seek medical treatment for headache relief [ 33 ].…”
Section: Discussionsupporting
confidence: 94%
“…Another study on medical students reported that effect on daily activities was higher in chronic tension headache (96.7%) and migraine without aura (94.6%) than migraine with aura (91.3%) and episodic tension headache (85.1%) [25].…”
Section: Discussionmentioning
confidence: 94%
“…The prevalence of TTH was found to be 40.3% in the current study within the global prevalence rate of 12%-78%. 22 Studies from Syria, 23 Turkey, 24 and Nigeria 25 reported much lower prevalence while another study from Saudi Arabia showed a similar prevalence. 26 For TTH, no significant difference was with age, sex, year of study, and staying with the hostel, which is supported by findings of Alkarrash et al, 23 Syria.…”
Section: Discussionmentioning
confidence: 96%